2019
DOI: 10.1590/1807-1929/agriambi.v23n1p60-64
|View full text |Cite
|
Sign up to set email alerts
|

Dual-stage sugar substitution in Tommy Atkins mango

Abstract: The dual-stage sugar substitution technique (D3S) was used to induce sugar replacement in mango. It involved two stages, in which high-calorie sugars were partially removed from the fruit samples in the first stage and, in the second one, low-calorie sugar was incorporated into the mango. Ultrasonic waves can be applied in one or both stages and their use was also evaluated in this study. Results showed that submitting samples to ultrasonic waves (25 kHz) in both stages and their immersion in Stevia-based solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Furthermore, as the cell wall has already been destabilized by ultrasonic waves in the first stage of the D3S, the incorporation of solutes will be facilitated in the subsequent stage, due to the concentration gradient existing between the fruit and the isomaltulose solution. Similar behavior was reported in D3S studies with mango (de Medeiros et al, 2019) and apple (Oliveira;Fernandes, 2012), in which it was observed that the application of ultrasound, in both stages, resulted in a gain in solids relatively higher than samples without ultrasonic treatment. Garcia-Noguera et al (2010) observed in their study that the incorporation of stevia in strawberries was greater when the second stage was carried out without ultrasound.…”
Section: Effect Of Pretreatmentssupporting
confidence: 84%
See 2 more Smart Citations
“…Furthermore, as the cell wall has already been destabilized by ultrasonic waves in the first stage of the D3S, the incorporation of solutes will be facilitated in the subsequent stage, due to the concentration gradient existing between the fruit and the isomaltulose solution. Similar behavior was reported in D3S studies with mango (de Medeiros et al, 2019) and apple (Oliveira;Fernandes, 2012), in which it was observed that the application of ultrasound, in both stages, resulted in a gain in solids relatively higher than samples without ultrasonic treatment. Garcia-Noguera et al (2010) observed in their study that the incorporation of stevia in strawberries was greater when the second stage was carried out without ultrasound.…”
Section: Effect Of Pretreatmentssupporting
confidence: 84%
“…The solids gain content in the D3S 4 process (4.809%) which consists of two stages assisted by ultrasound (both in the sugar removal stage and in the isomaltulose incorporation stage) was higher than other treatments. This behavior can be explained by the influence of ultrasonic waves on the cell wall, through the formation of microchannels and the cavitation process, which result in higher mass transfer rates between the fruit and the concentrated isomaltulose solution during the incorporation stage (de Medeiros et al, 2019;Garcia-Noguera et al, 2010). Furthermore, as the cell wall has already been destabilized by ultrasonic waves in the first stage of the D3S, the incorporation of solutes will be facilitated in the subsequent stage, due to the concentration gradient existing between the fruit and the isomaltulose solution.…”
Section: Effect Of Pretreatmentsmentioning
confidence: 99%
See 1 more Smart Citation